Creating a framework for a large-scale implementation of Content and Language Integrated Learning: The first steps. Issue 1 (2015) - Surmont, Jill; Struys, Esli; Somers, Thomas
Abstract : We argue that in order for the EU 2020 educational goals to be achieved, a large-scale implementation of Content and Language Integrated Learning (CLIL) is necessary. This educational approach not only ensures knowledge of multiple languages but it also stimulates pupils in such a way that they reach a higher cognitive level. To enable such large-scale implementation, a framework is needed that offers support and guidelines for the various countries and regions. This article presents the first steps towards such a supporting framework by presenting and applying four parameters that allow an analysis of the linguistic climate of a region/country. The makeup of a linguistic climate has a major influence on the way a language policy is held up, and therefore these parameters give an indication of where changes should be made to ensure a successful implementation of CLIL.